A antítese essencial: T.H. Huxley e o lugar da humanidade na natureza - Uchôa, Raphael B. S (2014)
The problem relative to man s place in nature operated as a common thread among several notions and theories formulated and debated in Victorian England. That was precisely the subject of Man s Place in Nature, a book by Thomas Henry Huxley (1825-1895) that became highly influential from the 1860s onwards. In addition, Huxley gave countless lectures, participated in hot public debates, and wrote essays and letters on that subject. The aim of the present study was to analyze contextual and epistemological features relative to Huxley s book. Following a mapping of the ideas on man s place in nature held in England in the first half of the 19th century up to the 1860s, Man s Place in Nature was subjected to epistemological analysis. Our results point to an overlapping of the ideas then formulated relative to zoological classification and appropriate criteria for comparison required for accurate grading of living beings, as e.g., the marks of animality . In this regard, Huxley prioritized the criteria provided by comparative anatomy and the current ideas on human races, as well as the traditional notions on the gradation of species and scale of nature , aiming at formulating a general law that would ensure the essential unity of humankind with the remainder of nature. Such general law was particularly necessary to demonstrate Huxley s hypothesis stating that there is no essential antithesis between human beings and the other animals, and that the physical, moral and mental differences between them do not suffice to posit an insurmountable gap between humankind and nature